Factors associated with nosocomial fungal sepsis among patients in the paediatric intensive care unit at the Chris Hani Baragwanath academic hospital - Ahn, Seung-Hye (My University, 2017)
Introduction Sepsis, and in particular, severe sepsis, remains a major cause of death in children worldwide. One of the areas where the burden of sepsis is keenly felt is in the paediatric intensive care unit (PICU) setting, contributing significantly to childhood mortality. Fungal organisms have emerged as a major organism contributing to nosocomial sepsis in PICU. No local data regarding nosocomial fungal sepsis in the non-neonatal, PICU population exists regarding this matter. This study describes the characteristics of patients with nosocomial fungal sepsis in the PICU at South Africa’s largest hospital Chris Hani Baragwanath Academic Hospital (CHBAH). Methods This study was a retrospective review of patient records. All patients aged 0-16 years admitted to the PICU at Chris Hani Baragwanath Academic Hospital (CHBAH) from January 2008 through December 2011 were assessed. A total of seventeen patients who developed nosocomial fungal sepsis were included in this study. Results The incidence of candidaemia was reported to be 3.2 per 100 cases. The major age group affected by nosocomial fungal sepsis was the under one age group. The most common diagnoses on admission were lower respiratory tract infection (LRTI) followed by haematology-oncology and acute gastroenteritis cases. ICU factors found to commonly co-‐exist with proven nosocomial fungal sepsis were presence of a central venous catheter (100%), mechanical ventilation (82%), arterial line (70%), and systemic corticosteroid use (47%). The penicillin class was the most common antimicrobial that patients were found to be on at the time of nosocomial sepsis. The most common fungal organism as a cause for nosocomial sepsis was C. parapsilosis rather than C. albicans. Furthermore, the majority of this study’s isolates were susceptible to voriconazole rather the current empiric antifungal of choice, namely fluconazole. Conclusion The presence of central venous catheters, arterial lines, mechanical ventilation and systemic corticosteroid use is common in paediatric patients with nosocomial fungal sepsis. However, this study was unable to determine statistically significant factors associated with fungal sepsis in a tertiary PICU due to the surprisingly small number of cases (n=35) detected over a four-year period. This perhaps represents the most striking finding of the study together with a concerning pattern of fluconazole resistance (14%) among isolated organisms.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Paediatrics and Child Health 29 May 2017
Keywords: Sepsis Paediatric Intensive Care Unit